Impact of Organizational Culture on Perceptionsof Career Success among Women - Małgorzata Kluska-Nowicka (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2025)
Aim: The objective of this study is to determine the impact of organizational culture on women’s career success and their perception of success, taking into account the interrelationships between variables.